2021
DOI: 10.1039/d1ra01420j
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of pH-controlled DNA–surfactant manipulation for biomolecules

Abstract: The cyclic process of the DNA extension–time curve measured by magnetic tweezers in releasing and stretching processes with different concentrations of DDAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…49 Based on these values, EP would dominate the movement, resulting in an effective movement towards the positive electrode, as was observed in our experiments. At this pH, as the 1 mM surfactant concentration is close to the CMC of the surfactant in non-ionic state, 41 some micelles are expected to get adsorbed at the oil droplet as well as the PDMS. This factor can further increase the effect of the interacting ions such as Cl − , OH − and Na + with the monomers.…”
Section: Resultsmentioning
confidence: 98%
“…49 Based on these values, EP would dominate the movement, resulting in an effective movement towards the positive electrode, as was observed in our experiments. At this pH, as the 1 mM surfactant concentration is close to the CMC of the surfactant in non-ionic state, 41 some micelles are expected to get adsorbed at the oil droplet as well as the PDMS. This factor can further increase the effect of the interacting ions such as Cl − , OH − and Na + with the monomers.…”
Section: Resultsmentioning
confidence: 98%
“…In a previous mechanical measurement of DNA–lysozyme complexes in optical tweezers [ 1 ], they found that the persistence length of DNA–lysozyme complexes exhibits a nonmonotonic behavior as a function of the protein concentration. We have studied DNA complexes at various ionic and solution conditions in the past [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] For example, nucleic acids could kink with special protein residues and ions to perform various mechanical properties and regulate their elasticity of themselves in protein recognition. Thus, the structural elasticities are important for the nucleic acids, which are affected by many factors, such as the ionic DOI: 10.1002/adts.202200534 environments, [9][10][11][12][13] temperature, [14][15][16] and sequence orders. [17][18][19][20][21] It is not surprising that many studies have been devoted to the investigation of nucleic acid elastic properties by molecular dynamics simulation and experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] The DNA elasticities have been investigated in various environments by experiment and computer simulation. [12,20,[35][36][37][38][39][40][41][42] For example, Qiang et al investigated the sequence-dependent of DNA elasticity for three typical AA-TT, AT-TA, and general sequences. These authors concluded [32] that in the three different sequences, polymer AA-TT chains owned a larger bending persistence length than others with only two sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation